Variation of carbohydrate intake in diabetic children on carbohydrate counting. (April 2019) - Robart, Elise; Giovannini-Chami, Lisa; Savoldelli, Charles; Baechler-Sadoul, Elysabeth; Gastaud, Frédérique; Tran, Antoine; Chevalier, Nicolas; Hoflack, Marie
Highlights: First study about variation of carbohydrate intake in diabetic children. Pediatric patients significantly vary their carbohydrate intake. Carbohydrate counting is justified in the pediatric population. Abstract: Aims: Carbohydrate counting (CC) is a technique for managing diabetes particularly based on the counting of carbohydrates. It allows diabetic patients to vary their amount of carbohydrates from one meal to another by adjusting their insulin dose. The primary objective was to determine the variation of carbohydrate intake (CI) in children on CC. Method: This was a prospective study conducted between 2014 and 2016. We collected the amount of carbohydrates eaten at each meal by 77 diabetic over a period of 28 days (i.e. 8068 data). We analyzed the number and percentage of significant CI variation rates from one day to another, both for the whole day and for each meal. The CI variation rate was deemed significant if it was greater than or equal to 30%. Results: The percentage of significant CI variation rates was 30% at the daily level, 34% for breakfast, 44% for lunch and dinner, and 53% for snack. The percentage of significant variation rates varied according to age, treatment and occurrence of events. Conclusion: Children varied their CI significantly from one meal to another more than one in three times. CC offers flexibility and a better quality of life for children using this method.